2022
DOI: 10.26630/jk.v13i1.2821
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Hubungan Usia, Masa kerja dan Pengetahuan terhadap Keluhan Musculoskeletal Disorders (MSDs)

Abstract: Workers are human resources who have a very influential and significant role in carrying out the production process, especially manual activities. The production process in a workplace still requires manual human handling in the process of work, but humans have abilities and limitations both physically and non-physically that are often related to musculoskeletal. The health problem that occupies the first position associated with the job is Musculoskeletal Disorders. Method: The design of the study used in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The higher a person's level of formal education, the easier it will be to absorb information, including health information, and the individual's awareness of healthy living behavior will also be higher. 19 This statement is supported by research by Indriyani et al (2022), Respondents were given an ergonomics knowledge questionnaire that had previously been tested for its validity and reliability. Respondents with scores above the median were stated to have good knowledge of ergonomics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation

Prevalence study of musculoskeletal disorders among bank workers

Gede Maheza Wiratama,
Made Hendra Satria Nugraha,
Ni Luh Nopi Andayani
2024
ptji
“…The higher a person's level of formal education, the easier it will be to absorb information, including health information, and the individual's awareness of healthy living behavior will also be higher. 19 This statement is supported by research by Indriyani et al (2022), Respondents were given an ergonomics knowledge questionnaire that had previously been tested for its validity and reliability. Respondents with scores above the median were stated to have good knowledge of ergonomics.…”
Section: Discussionmentioning
confidence: 97%
“…Complaints of no pain refer to the absence of any disturbance felt; somewhat painful refers to the presence of a slight disturbance in certain parts; pain refers to discomfort in 0.000, indicating that a person's level of ergonomics knowledge will influence their actions in efforts to prevent MSD complaints. 20 Data on the respondent's height and weight are used to measure BMI, which is then classified according to Asia-Pacific guidelines, namely underweight, normal, overweight, and obese. In this study, 9 people had an overweight BMI, 15 people had an obese BMI, and 16 others had a normal BMI.…”
Section: Methodsmentioning
confidence: 99%

Prevalence study of musculoskeletal disorders among bank workers

Gede Maheza Wiratama,
Made Hendra Satria Nugraha,
Ni Luh Nopi Andayani
2024
ptji
“…Work posture and temperature also affect work fatigue with p = 0.011, p = 0.045, and p = 0.023 in informal sector workers in Solor village, East Nusa Tenggara Odi, Purimahua, & Ruliati (2018). Work attitude and workload affect fatigue in public service workers in Makassar with a p-value = 0.001 (Indriyani, Badri, Oktariza, & Ramadhani, 2022;Rosmiati, Abdullah, & Nurlinda, 2021). Work attitude (p = 0.009 and working period (p = 0.002) are related to work fatigue in furniture workers in Tempe District, Wajo Regency (Wahyuni, Rasman, & Khaer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, workers with a long period of service will have more knowledge and experience. 19 Research by Fatejarum et al (2020) found that 65% of respondents with a working period of 5-10 years experienced musculoskeletal complaints, and the results showed that the longer a person's working period, the higher the perceived complaints due to repetitive work positions related to muscle fatigue. 20 The relationship between work duration per day and musculoskeletal complaints was also stated through research by A Fatejarum et al (2020), which shows a relationship between length of work and musculoskeletal complaints in farmers.…”
Section: Discussionmentioning
confidence: 99%